The Effect of Return on Assets, Current Ratio, and Debt to Equity Ratio on The Firm Value of Property and Real Estate Companies Listed on IDX for 2016-2020 Period - Eva Kartikasari; Subur Karyatun; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This study aims to determine the effect of Return on Assets (ROA), Current Ratio (CR), and Debt to Equity Ratio (DER) on the Company Value. This study was processed using eviews 9. This study uses secondary data by analyzing the financial statements and annual reports of 16 sample companies from 79 property and real estate companies listed on IDX for the 2016-2020 period. Sampling in this study used purposive sampling method. The results of this study indicate that partially, Return on Assets (ROA) has no effect on the company value of property and real estate companies listed on IDX for the 2016-2020 period, while the Current Ratio (CR) and Debt to Equity (DER) has a positive and significant effect on the company value of property and real estate listed on the IDX for the 2016-2020 period.